Paradigma Integratif-Holistik sebagai Model Transdisipliner Pendidikan Islam Abad ke-21: Kritik atas Keterbatasan Islamisasi Pengetahuan - Muhamad Amin; Hanik Yuni Alfiyah; Febriarsita Eka Sasmita (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
Islamic education in Indonesia is still hindered by the dichotomy of knowledge and a lack of integration between modern science and Islamic values. This study aims to analyze the direction of educational reform through a synthesis of the Islamization of knowledge and the integrative-holistic paradigm. Employing a qualitative library research method, it evaluates the thoughts of al-Faruqi, al-Attas, Fazlur Rahman, and Seyyed Hossein Nasr. The conceptual findings indicate that the integrative-holistic paradigm transcends the limitations of Islamization by offering a transdisciplinary framework that balances revelation, reason, and empiricism. Epistemological reconstruction based on tawḥīd is identified as the primary catalyst for transforming curricula and institutional governance. This study asserts that this model is more contextually relevant for Indonesia as it fosters a rational, spiritual, and contextual educational system. The research concludes that transitioning toward a value-oriented, transdisciplinary system is a vital instrument for the reconstruction of modern Islamic civilization.